Photometric Light Curve Analysis of ET Leo - Aven M. Hamedamen; Ismail M. Murad (Zanco Journal of Pure and Applied Sciences, 2019)
In this work, the short period system named (ET Leo) have been chosen to be analyzed with B , V and R light curves with the Wilson-Devinney code and the results of orbital parameters of the system were obtained and compared with those obtained from previous studies. The present results indicated that the selected system is a contact system and the absolute parameters of the components have been determined with suitable accuracy, for which the physical parameters have been obtained in a uniform way. Spot solution parameters have been evaluated for the binary system under investigation. The system shows asymmetries and peculiarities in the observed light curves.